Peran Notaris dalam Penyertaan Tanah Pelaba Pura sebagai Modal BUM Desa - Fajar, Ida Bagus Kade; Sudantra, I Ketut (Acta Comitas; Vol 8 No 03 (2023)DO - 10.24843/AC.2023.v08.i03.p7, 2023)
This research seeks to obtain an understanding and analysis regarding the role of notaries in the participation of Pelaba Pura land as capital for BUM Desa. This research was carried out based on the Normative legal research method with a statute approach and a conceptual approach by analyzing the concept of temple land and the legal provisions governing opportunities for its inclusion as BUM Desa capital. This research shows that the Pelaba Pura Land, as land owned by the Pura, has received recognition as a Religious Legal Entity so that it can become the subject of Land Ownership Rights through the Decree of the Minister of Home Affairs/KBPN No. SK.520.1/2252 can be included in BUM Desa capital through the Village community capital inclusion scheme. As an effort to provide certainty and legal protection for Pelaba Pura land, the results of the perarem or deliberation regarding the inclusion of Pelaba Pura Land as BUM Desa capital should be made in the form of an authentic notarial deed. Through this deed, it is hoped that it can clarify the basis for the use of temple land by BUM Desa so that it can reduce the potential for disputes or conflicts regarding the use of temple land in the future.